2022
DOI: 10.1007/s10729-022-09600-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of service quality and anticipated emotions on donor loyalty: an empirical analysis in blood centres in Spain

Abstract: Blood donation centres need to recruit and retain donors to ensure the effectiveness and efficiency of healthcare systems, as COVID-19 has recently evidenced. In such risky settings, blood donation services must increase donations. Service quality can increase donations but its evaluation only amounts to a cognitive evaluation, and not to an emotional appraisal. Consequently, both service quality and emotions should be considered when predicting donor behaviour. In fact, donating blood is an emotionally charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…An unexpected finding was that there was no significant positive correlation between attitude toward blood donation and willingness to donate, a finding that is different from established studies ( 62–64 ), which demonstrated a positive correlation between positive attitude toward blood donation and willingness to donate, but this study found no significant positive relationship between attitude and willingness to donate. It was hypothesized that there are other factors in the process of attitude to behavioral willingness to donate, such as fear of donating blood ( 65 ), anxiety about donating blood ( 66 ), anticipatory emotions ( 67 ), and the environment of donating blood ( 68 ), which are important factors affecting the public’s willingness to donate blood. Masser ( 45 ) demonstrated that there is a positive relevant relationship between attitude toward donating blood and self-efficacy, which is consistent with the hypotheses of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding was that there was no significant positive correlation between attitude toward blood donation and willingness to donate, a finding that is different from established studies ( 62–64 ), which demonstrated a positive correlation between positive attitude toward blood donation and willingness to donate, but this study found no significant positive relationship between attitude and willingness to donate. It was hypothesized that there are other factors in the process of attitude to behavioral willingness to donate, such as fear of donating blood ( 65 ), anxiety about donating blood ( 66 ), anticipatory emotions ( 67 ), and the environment of donating blood ( 68 ), which are important factors affecting the public’s willingness to donate blood. Masser ( 45 ) demonstrated that there is a positive relevant relationship between attitude toward donating blood and self-efficacy, which is consistent with the hypotheses of the present study.…”
Section: Discussionmentioning
confidence: 99%